Use of Hand Sanitizers in COVID-19 Prevention: A Comprehensive Overview - Suneetha Vuppu; Toshika Mishra; Arjun Chinamgari (MDPI AG, 2023)
The pandemic outbreak of Coronavirus disease 2019 (COVID-19) has drastically changed the picture of global healthcare. With the rapid emergence of novel variants of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) that rendered the currently available therapeutic and diagnostic approaches inefficient in containing the transmission of infection, it becomes important to focus on strategies to break the transmission chain. The major approach to contain the spread of infection is the promotion of adequate hand hygiene practices in public as hands are an important source of pathogenic microbes. Hand hygiene is an important part of everyday life for maintaining a healthy and disease-free lifestyle. With the outbreak of the pandemic, people are now understanding the importance of hand hygiene practices. The global market of hand sanitizers has experienced rapid growth and high demand. This review aims to discuss the use of sanitizers during the period of COVID-19 and their role in controlling the transmission of infection. It also focuses on global market trends, the advancements in the development of sanitizer formulations, and the limitations of commercial sanitizers. Therefore, the formulation of an effective hand disinfectant is crucial for preventing future pandemic outbreaks.